Music Therapy as a supporting method in the treatment of bipolar disorder - Oliwia; Agnieszka Ewelina Wojciechowska; Marek Jarosław Molenda; Maria Wachowska; Marta Szymura; Mateusz Paniak; Mateusz Romaniuk; Michał Brunon Krawczyk; Paweł Maciej Rycąbel; Wojciech Jan Sowiński (Journal of Education, Health and Sport)
Bipolar disorder is a mental illness that affects people of all ages and both sexes equally. Psychiatry primarily relies on conventional treatments such as pharmacotherapy, electroconvulsive therapy, and psychotherapy to manage bipolar disorder. However, despite their effectiveness and many benefits, these methods may not always be sufficient—especially in treatment-resistant cases.